Viscous fragmentation and topology-induced residual gas trapping during gas–water displacement in fracture networks - Kangsheng Xue; Hai Pu; Yanlong Chen; Ming Li; Yu Wu; Lulu Liu; Qingyu Yi; Zheng Ma (Advances in Water Resources, 2026)

Social Arousal and Interspecific Calf Handling by Short‐finned Pilot Whales - Agathe Serres; Mingming Liu; Mingli Lin; Hongri Wang; Xiuqing Hao; Songhai Li (Marine Mammal Science, 2026)

Integrated Physiological, Transcriptomic, and Gut Microbial Responses of Chinese Mitten Crab (Eriocheir sinensis) to Acute Salinity Stress - Yiming Li; Yucong Ye; Zongli Yao; Yan Li; Pengcheng Gao; Zhen Sun; Yuxing Wei; Kai Zhou; Binhong Guo; Yunlong Zhao; Qifang Lai (Marine Biotechnology, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Coupling fracture extraction and network topology for structure-controlled rockfall hazard assessment in complex terrain - Yu Huang; Hongwei Li; Pengtao Zhou; Shiyu Zhang; Weiming Liu (Natural Hazards, 2026)

Targeting FAR1 to inhibit intestinal macrophage ferroptosis: repurposing irinotecan as a novel sepsis therapy - Haoyue Deng; Weifei Wang; Qinghui Li; Xinming Xiang; Yu Zhu; Zisen Zhang; Xiaowei Zhou; Yue Wu; Jie Zhang; Liangming Liu; Tao Li (Apoptosis, 2026)

Luteolin ameliorates sympathetic stress-induced myocardial injury by inhibiting the VEGFA/VEGFR2 and PI3K/Akt/NF-kappaB signaling pathways - Sheng Li; Yanli Guo; Peiyao Yang; Yaming Liu; Xinzhi Li; Ketao Ma; Li Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Predicting big five personality traits from resting-state EEG connectivity: a connectome predictive modeling study - Chu Zhang; Yao Liu; Yiting Long; Siyuan Hu; Ming Li; Wenkai Bai; Yiting Li; Can Cui; Can Gao (Brain Structure and Function, 2026)

Grass carp reovirus utilizes multiple endocytic pathways for host cell entry - Xiaowen Zou; Yongming Li; Zuoyan Zhu; Yaping Wang; Libo He (Aquaculture, 2026)

Biological nitrification inhibition and microbial community response to Moringa seed extract in controlled greenhouse soils - Mingxia Yang; Ningning Zhou; Lin Ma; Zi He; Jia Zhao; Aiming Liu; Jianbin Zhou; Xiaofang Deng (Applied Soil Ecology, 2026)

Cross-domain microbial interactions mediate soil multifunctionality during crop growth stages - Guo Chen; Chao Chang; Zihan Yan; Hao Wang; Qingwei Zhang; Jian Wang; Ming Li; Wei Zheng; Ding He; Biao Zhu (Applied Soil Ecology, 2026)

Three decades of green manure rotations sustain soil nitrogen supply by microbial functional restructuring under reduced mineral fertilization - Lu Yang; Jia Liu; Junjie Huang; Zhan Jiang; Ming Liu; Weidong Cao (Applied Soil Ecology, 2026)

Revealing the mechanism of Burkholderia sp. Pyr-1 driven removal of pyraclostrobin-contamination through soil microbial community function and assembly - Hongming Liu; Siwen Wang; Zhengqi Zhang; Xiang Li; Yujie Ren; Yuanxiu Wang; Junwei Huang; Lina Sun (Applied Soil Ecology, 2025)

Toxicity of polyethylene microplastics and atrazine to microorganisms in soil and gut of earthworms - Hao Jia; Siqi Zhou; Ning Lei; Guanghui Sun; Ming Li (Applied Soil Ecology, 2025)

The interaction between mycorrhiza and phoD-harbouring bacteria influencing soil available phosphorus in Pinus massoniana plantations - Lifen Li; Yueming Liang; Qiang Li; Fujing Pan; Zhangqi Yang; Yanlan Wei; Yijing Li; Yanjun Chen; Hanlian Qin; Guangping Xu (Applied Soil Ecology, 2025)

Biogeographical patterns of antibiotic resistomes in soil biocrusts from urban green spaces at the continental scale - Yulong Li; Qin Chen; Chao Chang; Mian Zhang; Ming Li; Langjun Cui (Applied Soil Ecology, 2025)

Integrating analytical solutions and U-Net model for predicting groundwater contaminant plumes in pump-and-treat systems - Xuehang Song; Inci Demirkanli; Zhangshuan Hou; Xinming Lin; Marinko Karanovic; Matt Tonkin; Delphine Appriou; Rob Mackley (Advances in Water Resources, 2025)

Divergent effects of biomass-derived carbon dots application and sweetpotato planting on accumulations of soil microbial necromass carbon in Vertisol - Jing Wang; Meng Zhu; Xiaoya Zhu; Qiangqiang Zhang; Yongchao Yu; Peng Zhao; Ming Liu; Rong Jin; Zhonghou Tang (Applied Soil Ecology, 2025)

Spatial dynamics of soil algae: Insights into abundance, community structure, and ecological roles in mixed biocrusts across China - Chao Chang; Li Gao; Arash Zamyadi; Hao Wang; Ming Li (Applied Soil Ecology, 2025)

The effects of a combination of maize/peanut intercropping and residue return on soil microbial nutrient limitation in maize fields - Fanyun Yao; Wei Qi; Yujun Cao; Jie Liang; Xiaodan Liu; Zhiming Liu; Yanjie Lv; Wenwen Wei; Wenhua Xu; Yang Yu; Xiang Li; Jian Feng; et al. (Applied Soil Ecology, 2025)

Origin and assembly characteristics of periphyton microbes in subtropical paddy fields: A case study in Tuojia catchment in Southern China - Zongming Li; Jie He; Jianlin Shen; Yanyan Li; Quan Yuan; Qihong Zhu; Jinshui Wu (Applied Soil Ecology, 2025)

Litter quality regulates cover crop litter decay alongside altered microbial facets - Guilong Li; Ke Leng; Wenjing Qin; Xiaofen Chen; Yongxin Lin; Ming Liu; Meng Wu; Jianbo Fan; Xiaoyue Wang; Yuji Jiang; Jia Liu (Applied Soil Ecology, 2024)

Long-term stationary fertilization decreased soil health in field-grown sweetpotato by increasing soil-borne diseases or allelochemicals - Xiaoya Zhu; Peng Zhao; Jing Wang; Qiangqiang Zhang; Yongchao Yu; Ming Liu; Rong Jin; Zhonghou Tang (Applied Soil Ecology, 2024)

Straw returning and reducing nitrogen application rates maintain maize yields and reduce gaseous nitrogen emissions from black soil maize fields - Fang Song; Ming Liu; Zhijuan Qi; Zhongxue Zhang; Bai Wang; Zhihao Yin; Jingwen Xu; Jialu Sun (Applied Soil Ecology, 2024)

Pore-scale investigation of solute dispersion behavior in porous media under a two-phase co-flow condition - Chunwei Zhang; Kai Zhang; Jiale Mo; Zijing Li; Tetsuya Suekane; Yuncong Wang; Ming Li (Advances in Water Resources, 2024)

Numerical investigation of solute migration and release from sediments driven by wave-induced accumulation of pore water pressure - Xiaoli Liu; Shouming Liu; Hongyi Zhao; Dong-Sheng Jeng; Longtao Guo; Tianyuan Zheng (Advances in Water Resources, 2023)

Analytical solution of three-dimensional particle transport in porous media considering a dual deposition mode - Shujie Tu; Xiaoming Liu; Hongjiang Cai; Zexi Yang (Advances in Water Resources, 2023)

Cultivation of fish ciliate parasites: Progress and prospects - Ming Li; Giana Bastos Gomes; Weishan Zhao; Guangran Hu; Ke Huang; Tomoyoshi Yoshinaga; Theodore G. Clark; Wenxiang Li; Hong Zou; Shangong Wu; Guitang Wang (Reviews in Aquaculture, 2023)
Ciliates are considered the most harmful parasites of fish, causing mass mortalities and thus substantial economic losses to the aquaculture and ornamental fish industries. To better elucidate their pathogenic mechanisms and facilitate the development of effective prevention and control strategies, it is essential to apply novel technologies to ensure the continuous and sufficient supply of parasite specimens. This review discusses the latest research progress in the artificial culture of six important parasitic ciliates affecting both freshwater and marine fish globally: Ichthyophthirius multifiliis , Cryptocaryon irritans , Chilodonella ( C. hexasticha , C. piscicola and C. uncinata ), Balantidium ctenopharyngodoni , Scuticociliatida gen. spp., and Tetrahymena spp. Methods for in vitro and in vivo culture as well as cryopreservation/preservation (depending on the specific species) of these organisms are described herein. Challenges and future applications of parasite culture are also discussed.

Cover Image - Ming Li; Giana Bastos Gomes; Weishan Zhao; Guangran Hu; Ke Huang; Tomoyoshi Yoshinaga; Theodore G. Clark; Wenxiang Li; Hong Zou; Shangong Wu; Guitang Wang (Reviews in Aquaculture, 2023)

Developing a baseline and tools for the future assessment of the ecological status of rivers within the Three Gorges Reservoir catchment, China - Shi-yun Chi; Ju-xiang Hu; Ming Li; Jin-xiu Zheng (Hydrobiologia, 2016)